Factors Influencing Excessive Daytime Sleepiness among Undergraduate Nursing Students: A Cross-Sectional Study from North Sulawesi, Indonesia - Saluy, Priscillia M.; Lainsamputty, Ferdy; Wu, Bo-Hsun (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2025)
Background: Excessive daytime sleepiness (EDS) is a common yet underrecognized concern among nursing students, potentially impairing academic performance and clinical readiness. Identifying factors associated with EDS is essential to inform preventive strategies and promote optimal student functioning. Objective: This study aimed to identify the factors influencing EDS among undergraduate nursing students in North Sulawesi, Indonesia. Methods: A descriptive correlational, cross-sectional design was employed. This study involved 101 students from a university in North Sulawesi Province, Indonesia, selected through consecutive sampling. Data were collected using the Epworth Sleepiness Scale (ESS) and analyzed using descriptive statistics, the Mann–Whitney U test, Kruskal–Wallis H test, Spearman’s correlation, and multiple linear regression. Results: The mean ESS score was 12.98 (SD=4.07), with 71 respondents (70.3%) classified as experiencing EDS. Caffeine consumption (B=3.458, β=0.295, 95% CI [1.232, 5.684], p=0.003) significantly predicted EDS, accounting for 14.9% of the variance. Conclusion: These findings highlight the need to address modifiable lifestyle factors, particularly caffeine intake, to reduce EDS among nursing students. Nurse educators and academic institutions should implement sleep health education and promote healthy coping strategies to mitigate daytime sleepiness. Early intervention may enhance students’ academic performance and clinical competence, ultimately improving patient safety and quality of care in future nursing practice.